Do Taxes Matter for Long-Run Growth? : Harberger's Superneutrality Conjecture - Asea, Patrick; Mendoza, Enrique; Milesi-Ferretti, Gian. (Washington, D.C. : International Monetary Fund, 1995)
Harberger's superneutrality conjecture contends that, although in theory the mix of direct and indirect taxes affects investment and growth, in practice growth effects of taxation are negligible. This paper provides evidence in support of this view by testing the predictions of endogenous growth models driven by human capital accumulation. The theoretical analysis highlights implications of different taxes for growth and investment in these models. The empirical work is based on cross-country regressions and numerical simulations, using a new methodology for estimating aggregate effective tax rates. Results show significant investment effects from income and consumption taxes that are consistent with small growth effects. The results are robust to the introduction of other growth determinants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet